2010
DOI: 10.1111/j.1464-410x.2009.08822.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in peak urinary flow and voiding efficiency in men with signs and symptoms of benign prostatic hyperplasia during once daily tadalafil treatment

Abstract: The database was retained by the sponsor, but the investigators had access to the complete database. The statistical analyses were performed by the sponsoring company's statistician and reviewed and approved by all authors. The authors assume full responsibility for the completeness and accuracy of the content of the manuscript. This clinical trial was registered on clinicaltrials.gov with registration number: NCT00384930

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 23 publications
(36 reference statements)
3
49
0
2
Order By: Relevance
“…Finally, eight studies (from nine publications) [13,14,15,16,17,18,19,20,21] that enrolled 2,913 patients (1,871 tadalafil and 1,042 placebo) were included in the present meta-analysis. The process for the selection of relevant trials was performed as shown in figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, eight studies (from nine publications) [13,14,15,16,17,18,19,20,21] that enrolled 2,913 patients (1,871 tadalafil and 1,042 placebo) were included in the present meta-analysis. The process for the selection of relevant trials was performed as shown in figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies [13,14,15,16,17,18,19,20,21] evaluated the change in IPSS, and five studies [13,14,15,19,20] evaluated the change in the IIEF score from baseline to the endpoint for tadalafil. According to the participants who reported having ED at baseline, the two analyses were divided into two subgroups: group BPH (patients with BPH) and group BPH&ED (patients with comorbid BPH and ED).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have demonstrated that PDE5 inhibitors can improve lower urinary tract symptoms (LUTS) and urodynamic parameters [3,4,5]. These indications may be sufficient to convince physicians to prescribe PDE5 inhibitors once daily to patients with erectile dysfunction (ED) with or without concomitant LUTS.…”
Section: Introductionmentioning
confidence: 99%